Behaviour of Concrete Using Bottom Ash as Fine Aggregate - Dr.M.Harihanandh, Dr.R.Gopi, Dr.M.Saravanan (International Journal of Advanced Science and Technology, 2020)
Cement is the mostly used construction materials in the world. The utilisation of concrete attains the second place next to water utilisation. Concrete is the most highly consumed substance about 600 crore tons created every year. In this century, the concrete has treated as the foremost building material for the infrastructure needs. In the present scenario, no construction activity can be imagined without using concrete, the reason is its high strength and durability. Fine aggregate scarcity is increasing day to day activities of construction work. So, the alternate for fine aggregate has to be found. Here, the bottom ash is the waste matter derived from the thermal power plants and used as substitute material for fine aggregate. In order to achieve the theme, the bottom ash has replaced with fine aggregate in the concrete by 25%, 50% and 100%. Also the fresh concrete and hardened concrete properties were studied; the test results are compared with usual concrete (CC) specimens. The above work was carried on M25 grade mix.